Secondary battery and preparation method thereof
By coating the porous materials of covalent and hydrogen bonded organic frames on both sides of the battery separator, the gas generated inside the battery is absorbed, which solves the problem of deterioration of battery performance and safety, and achieves improvement of battery performance and safety guarantees.
Patent Information
- Application Number
- CN202411620182.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The side reactions generated by the secondary battery during charging and discharging lead to the accumulation of gas inside the battery, leading to deterioration of battery performance and safety issues. The existing solutions are limited in effect and high in cost.
The separator of the battery is coated with covalent organic frame porous materials and hydrogen bonded organic frame porous materials, which are used to adsorb CO2, CO, O2 on the positive electrode side and alkane and olefin gases on the negative electrode side to adjust the coating thickness To optimize porosity, achieve the best gas adsorption effect.
Effectively prevent the accumulation of gas inside the battery, improve battery performance, ensure safe use of the battery, and reduce battery performance deterioration and safety risks.
Smart Images

Figure CN119133776A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of photovoltaic technology, and mainly to a secondary battery and a preparation method thereof. Background Art
[0002] In the normal charging and discharging process of secondary batteries, especially lithium-ion batteries, in addition to the insertion / extraction (or alloying / de-alloying) reaction between lithium ions and active materials, there are also side reactions between the electrolyte and the active materials. These side reactions are inevitably accompanied by the generation of gases, such as O2, CO2, and CO gases usually generated near the positive electrode side, and alkane (such as CH4, C2H6) and olefin (such as C2H4, C3H6) gases generated near the negative electrode side. The accumulation of these gases will not only lead to an increase in the internal pressure of the battery, but may also cause safety problems such as battery swelling and internal short circuit, seriously affecting the performance and life of the battery.
[0003] In order to alleviate this problem, some solutions have been proposed. For example, by optimizing electrode materials, improving battery structure, and formulating reasonable charging and discharging systems to reduce the occurrence of side reactions. However, these methods have limited effects in practical applications and often fail to balance battery performance and cost.
[0004] In addition, some studies have attempted to introduce specific adsorbent materials into the battery separator to adsorb the gases generated during the battery cycle. For example, porous materials are set in the negative electrode active material layer, or nanofillers such as metal organic framework compounds (MOFs) are used in the separator to adsorb gases.
[0005] However, these methods have problems such as complex preparation, high cost, limited adsorption effect or possible impact on battery performance.
[0006] The present application provides a secondary battery and a method for preparing the same, which solves the problem of battery performance deterioration caused by gas generation inside the battery and affecting the safe use of the battery. Summary of the invention
[0007] In order to solve the problem of battery performance deterioration caused by gas production inside the battery and affecting the safe use of the battery, the present application provides a secondary battery and a preparation method thereof. The secondary battery includes a positive electrode, a negative electrode, an electrolyte and a diaphragm, the diaphragm is arranged between the positive electrode and the negative electrode, the diaphragm includes a base film, a first porous coating is arranged on the side of the base film close to the positive electrode, the first porous coating includes a covalent organic framework porous material, and a second porous coating is arranged on the side of the base film close to the negative electrode, the second porous coating includes a hydrogen bond organic framework porous material.
[0008] By coating organic porous framework materials with different gas adsorption properties on both sides of the base membrane, these porous materials have certain specificity for gas adsorption. For example, the covalent organic framework porous material coated on the base membrane near the positive electrode side has a strong adsorption effect on gases such as CO2, CO, and O2. The hydrogen bond organic framework porous material coated on the base membrane near the negative electrode side has a good adsorption effect on the above-mentioned alkane and olefin gases.
[0009] By adjusting the thickness of the coating, the porosity of the composite membrane can be adjusted to obtain the best gas adsorption effect, avoid the impact of gas production on the performance of lithium-ion batteries, effectively prevent the deterioration of battery performance caused by gas production inside the battery, ensure the safe use of the battery, and solve the problem of battery performance deterioration caused by gas production inside the battery and affecting the safe use of the battery.
[0010] Optionally, the thickness of the first porous coating layer is 0.1 μm to 2 μm, the thickness of the second porous coating layer is 0.2 μm to 0.3 μm, and the thickness of the base film is 4 μm to 30 μm.
[0011] Optionally, the covalent organic framework porous material is one or more of COF-1, COF-5, COF-10, COF-8 or COF-102.
[0012] Optionally, the hydrogen-bonded organic framework porous material is one or more of HOF-14, HOF-16, ZJU-HOF-1, ZJU-HOF-10 or HOF-FJU-1.
[0013] Optionally, the base membrane is a ceramic base membrane, a polyethylene base membrane, a polypropylene base membrane, a polypropylene / polyethylene / polypropylene multilayer base membrane, a polyethylene terephthalate base membrane, a polyacrylonitrile base membrane, a glass fiber base membrane, a cellulose base membrane, a polyvinylidene fluoride based membrane, a polyolefin membrane or a non-woven fabric membrane.
[0014] The present application also provides a method for preparing a secondary battery, which is used to prepare any of the secondary batteries described above, comprising: dissolving electrospun nanofibers in a polar organic solvent, stirring, and obtaining a preparatory electrospinning solution; adding a covalent organic framework porous material to part of the preparatory electrospinning solution, stirring, and obtaining a first blended membrane electrolyte; adding a hydrogen bond organic framework porous material to the remaining preparatory electrospinning solution, stirring, and obtaining a second blended membrane electrolyte; electrospinning the first blended membrane electrolyte on the side of the base membrane close to the positive electrode, and electrospinning the second blended membrane electrolyte on the side of the base membrane close to the negative electrode, and performing plasma treatment to obtain a diaphragm; assembling the diaphragm, the positive electrode, the negative electrode, and the electrolyte, and packaging them to obtain the secondary battery.
[0015] Optionally, the method further comprises: dissolving the electrospun nanofibers in a polar organic solvent, stirring for 2 h to 4 h until the mixture is uniformly mixed, to obtain a preliminary electrospinning solution, wherein the mass ratio of the polar organic solvent to the electrospinning nanofibers is 10:1 to 20:1, and the polar organic solvent is one or more of dimethylformamide, dimethylacetamide dimethyl sulfoxide, cyclopentane sulfone, ethyl nitrate, diethylformamide, and N-methylpyrrolidone; adding the covalent organic framework porous material to the preliminary electrospinning solution, ultrasonically stirring for 4 h to 8 h, and then standing at room temperature for 6 h to 8 h. A first blended membrane electrolyte is obtained; the hydrogen-bonded organic framework porous material is added to the prepared electrospinning solution, ultrasonically stirred for 4 hours to 8 hours, and then allowed to stand at room temperature for 6 hours to 8 hours to obtain a second blended membrane electrolyte; the first blended membrane electrolyte is electrospun on the side of the base membrane close to the positive electrode, and the second blended membrane electrolyte is electrospun on the side of the base membrane close to the negative electrode, and a diaphragm is obtained after plasma treatment with a non-polymerizable inorganic gas, wherein the non-polymerizable inorganic gas comprises one or more of O2, N2, CO2, CO, and H2O, and the pressure of the plasma treatment is 80 W to 120 W, and the treatment time is 40 s to 120 s; the diaphragm, positive electrode, negative electrode and electrolyte are assembled and packaged to obtain the secondary battery.
[0016] Optionally, in the first blended membrane electrolyte, the mass ratio of the covalent organic framework porous material to the electrospun nanofibers is 1:1~40:1, and in the second blended membrane electrolyte, the mass ratio of the hydrogen bonded organic framework porous material to the electrospun nanofibers is 1:1~40:1.
[0017] Optionally, the external voltage of the electrospinning is 10 kV ~ 25 kV, and the extrusion speed is 1 mL·h -1 ~2.5 mL·h -1 The collector is in the shape of a roller, the distance between the extrusion tube and the collector is 10 cm to 20 cm, and the collection speed of the roller is 50 rpm to 300 rpm.
[0018] Optionally, the first blended membrane electrolyte is electrospun on a side of the base membrane close to the positive electrode to a thickness of 0.1 μm to 2 μm, and the second blended membrane electrolyte is electrospun on a side of the base membrane close to the negative electrode to a thickness of 0.2 μm to 0.3 μm.
[0019] The present application provides a secondary battery and a method for preparing the same. The secondary battery comprises a positive electrode, a negative electrode, an electrolyte and a separator, wherein the separator is arranged between the positive electrode and the negative electrode, and the separator comprises a base film, a first porous coating is arranged on a side of the base film close to the positive electrode, and the first porous coating comprises a covalent organic framework porous material, and a second porous coating is arranged on a side of the base film close to the negative electrode, and the second porous coating comprises a hydrogen bond organic framework porous material.
[0020] Organic porous framework materials with different gas adsorption properties are coated on both sides of the base film. These porous materials have certain specificity and high efficiency in gas adsorption. For example, the covalent organic framework porous material coated on the base film near the positive electrode side has a strong adsorption effect on gases such as CO2, CO, and O2, and the hydrogen bond organic framework porous material coated on the base film near the negative electrode side has a good adsorption effect on the above-mentioned alkane and olefin gases.
[0021] The above materials can effectively absorb gas, solving the problem of battery performance deterioration caused by gas production inside the battery and affecting the safe use of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solution of the present application, the following briefly introduces the drawings required for use in the embodiments. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Figure 1 A schematic diagram of the structure of a secondary battery separator provided in an embodiment of the present application; Figure 2 A schematic diagram of the winding core structure of a secondary battery provided in an embodiment of the present application; Legend: Among them, 1-first porous coating layer; 2-base film; 3-second porous coating layer. DETAILED DESCRIPTION
[0023] The following embodiments are described in detail, and examples thereof are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following embodiments do not represent all implementations consistent with the present application. They are only examples of systems and methods consistent with some aspects of the present application as detailed in the claims.
[0024] In order to solve the problem of battery performance deterioration caused by internal gas generation in the battery and affecting the safe use of the battery, the present application provides a secondary battery and a preparation method thereof. The secondary battery comprises a positive electrode, a negative electrode, an electrolyte and a diaphragm, and the diaphragm is arranged between the positive electrode and the negative electrode.
[0025] like Figure 1 As shown, the diaphragm includes a base membrane 2, a first porous coating 1 is arranged on a side of the base membrane 2 close to the positive electrode, and the first porous coating 1 includes a covalent organic framework porous material, and a second porous coating 3 is arranged on a side of the base membrane 2 close to the negative electrode, and the second porous coating 3 includes a hydrogen bond organic framework porous material.
[0026] Covalent organic frameworks (COFs) are a new type of porous material constructed from organic components through dynamic covalent bonds. They have the characteristics of diverse structural designs, large specific surface area, ordered porous structure, strong stability and an expandable π-conjugated skeleton.
[0027] Hydrogen-bonded organic frameworks (HOFs) are a new type of flexible porous crystalline materials self-assembled from organic or metal-organic components through hydrogen bonds.
[0028] The ordered pores in the HOFs structure can serve as channels for gas storage / separation and ion conduction, and functional HOFs can be designed, especially through cooperative molecular design and post-modification.
[0029] Compared with metal-organic framework materials (MOFs), COFs materials are composed of organic monomers connected by covalent bonds, have high surface area, porosity and adjustability, and their structure is more stable than MOFs materials; HOFs have high solution processing performance, are easy to purify, have good thermal stability, have good biocompatibility, are easy to recover and reuse through simple recrystallization, and can achieve self-repair of materials, etc.
[0030] Moreover, compared with MOFs materials, there are no metal ions in the framework of HOFs materials and COFs materials. When used in secondary batteries, the impact of metal elements introduced into the material itself on battery performance can be avoided.
[0031] By coating organic porous framework materials with different gas adsorption properties on both sides of the base membrane, these porous materials have certain specificity for gas adsorption. For example, the porous material coated on the base membrane near the positive electrode side has a strong adsorption effect on gases such as CO2, CO, and O2. The porous material coated on the base membrane near the negative electrode side has a good adsorption effect on the above-mentioned alkane and olefin gases.
[0032] At the same time, by adjusting the thickness of the coating, the porosity of the composite membrane can be adjusted to obtain the best gas adsorption effect, avoid the impact of gas production on the performance of lithium-ion batteries, effectively prevent the deterioration of battery performance caused by internal gas production in the battery, ensure the safe use of the battery, and solve the problem of battery performance deterioration caused by internal gas production in the battery and affecting the safe use of the battery.
[0033] In some embodiments, the thickness of the first porous coating layer is 0.1 μm to 2 μm, the thickness of the second porous coating layer is 0.2 μm to 0.3 μm, and the thickness of the base film is 4 μm to 30 μm.
[0034] For example, the thickness of the first porous coating layer may be 0.15 μm, 0.18 μm, 0.25 μm, 0.6 μm, 1 μm, 1.5 μm, 1.75 μm, or 1.9 μm.
[0035] The thickness of the second porous coating layer may be 0.21 μm, 0.22 μm, 0.26 μm, 0.28 μm, or 0.29 μm.
[0036] The thickness of the base film may be 5 μm, 7 μm, 18 μm, 20 μm, 25 μm, or 29 μm.
[0037] In some embodiments, the thickness of the first porous coating layer is 0.12 μm to 0.19 μm, and the thickness of the second porous coating layer is 0.24 μm to 0.29 μm.
[0038] In some embodiments, the base film has a thickness of 5 μm to 28 μm.
[0039] In some embodiments, the thickness of the first porous coating layer is 1.5 μm, and the thickness of the second porous coating layer is 0.25 μm.
[0040] In some embodiments, the base film has a thickness of 25 μm.
[0041] In some embodiments, the covalent organic framework porous material is one or more of COF-1, COF-5, COF-10, COF-8 or COF-102.
[0042] In some embodiments, the hydrogen-bonded organic framework porous material is one or more of HOF-14, HOF-16, ZJU-HOF-1, ZJU-HOF-10, or HOF-FJU-1.
[0043] In some embodiments, the physical and chemical properties of the covalent organic framework porous material are shown in Table 1, and the physical and chemical properties of the hydrogen bond organic framework porous material are shown in Table 2.
[0044] Table 1 Physical and chemical properties of covalent organic framework porous materials
[0045] Table 2 Physicochemical properties of hydrogen-bonded organic framework porous materials
[0046] The pore size refers to the diameter or size of the internal pores of the hydrogen-bonded organic framework porous material, usually expressed in angstroms (Å). The internal pores can be circular pores or non-circular pores (such as diamond pores or other irregular pores). For example, "24.1×31.2" means that the diagonal lengths of the diamond pores are 24.1Å and 31.2Å respectively, and "6.7" means that the diameter of the circular pore is 6.7Å.
[0047] In some embodiments, the base film is a ceramic base film, a polyethylene (PE) base film, a polypropylene (PP) base film, a polypropylene / polyethylene / polypropylene multilayer base film, a polyethylene terephthalate (PET) base film, a polyacrylonitrile (PAN) base film, a glass fiber base film, a cellulose base film, a polyvinylidene fluoride (PVDF) base film, a polyolefin film or a non-woven fabric separator. Among them, the polypropylene / polyethylene / polypropylene multilayer base film refers to a multilayer base film in which a polypropylene film, a polyethylene film and a polypropylene film are stacked in sequence.
[0048] The present application also provides a method for preparing a secondary battery, which is used to prepare any of the secondary batteries described above, comprising: dissolving electrospun nanofibers in a polar organic solvent, stirring, and obtaining a preparatory electrospinning solution; adding a covalent organic framework porous material to part of the preparatory electrospinning solution, stirring, and obtaining a first blended membrane electrolyte; adding a hydrogen bond organic framework porous material to the remaining preparatory electrospinning solution, stirring, and obtaining a second blended membrane electrolyte; electrospinning the first blended membrane electrolyte on the side of the base membrane close to the positive electrode, and electrospinning the second blended membrane electrolyte on the side of the base membrane close to the negative electrode, and performing plasma treatment to obtain a diaphragm; assembling the diaphragm, the positive electrode, the negative electrode, and the electrolyte, and packaging them to obtain the secondary battery.
[0049] Among them, electrospinning refers to electrostatic spinning.
[0050] In some embodiments, the method further includes: dissolving the electrospun nanofibers in a polar organic solvent, stirring for 2h to 4h until the mixture is uniformly mixed, to obtain a preparatory electrospinning solution, wherein the mass ratio of the polar organic solvent to the electrospinning nanofibers is 10:1 to 20:1, and the polar organic solvent is one or more of dimethylformamide, dimethylacetamide dimethyl sulfoxide, cyclopentane sulfone, ethyl nitrate, diethylformamide, and N-methylpyrrolidone; adding the covalent organic framework porous material to part of the preparatory electrospinning solution, ultrasonically stirring for 4h to 8h, and then standing at room temperature for 6h to 8h. h, to obtain a first blended membrane electrolyte; add the hydrogen-bonded organic framework porous material to the remaining prepared electrospinning liquid, ultrasonically stir for 4h~8h, and then stand at room temperature for 6h~8h to obtain a second blended membrane electrolyte; electrospin the first blended membrane electrolyte on the side of the base membrane close to the positive electrode, and electrospin the second blended membrane electrolyte on the side of the base membrane close to the negative electrode, and perform plasma treatment with a non-polymerizable inorganic gas to obtain a diaphragm, wherein the non-polymerizable inorganic gas includes one or more of O2, N2, CO2, CO, and H2O, and the pressure of the plasma treatment is 80 W~120W, and the treatment time is 40 s~120s; assemble the diaphragm, positive electrode, negative electrode and electrolyte, and after packaging, obtain the secondary battery.
[0051] Long-term ultrasonic stirring can ensure that the nanofibers are uniformly dissolved in the organic solvent, that the porous organic framework material does not have large particle agglomerations, and that it is uniformly dispersed in the electrospinning liquid, that there are no bubbles in the mixed electrospinning liquid, and that a uniform diaphragm is obtained.
[0052] In some embodiments, in the first blended membrane electrolyte, the mass ratio of the covalent organic framework porous material to the electrospun nanofiber is 1:1~40:1, and in the second blended membrane electrolyte, the mass ratio of the hydrogen bonded organic framework porous material to the electrospun nanofiber is 1:1~40:1.
[0053] In some embodiments, in the first blended membrane electrolyte, the mass ratio of the covalent organic framework porous material to the electrospun nanofibers is 2:1 to 26:1.
[0054] In some embodiments, in the first blended membrane electrolyte, the mass ratio of the covalent organic framework porous material to the electrospun nanofibers is 25:1.
[0055] In some embodiments, in the second blended membrane electrolyte, the mass ratio of the hydrogen-bonded organic framework porous material to the electrospun nanofibers is 3:1 to 31:1.
[0056] In some embodiments, in the second blended membrane electrolyte, the mass ratio of the hydrogen-bonded organic framework porous material to the electrospun nanofibers is 30:1.
[0057] In some embodiments, the external voltage of the electrospinning is 10 kV to 25 kV, and the extrusion speed is 1 mL·h -1 ~2.5mL·h -1 The collector is in the shape of a roller, the distance between the extrusion tube and the collector is 10 cm to 20 cm, and the collection speed of the roller is 50 rpm to 300 rpm.
[0058] In some embodiments, the external voltage of the electrospinning is 15 kV to 23 kV, and the extrusion speed is 1.2 mL·h -1 ~2.3mL·h -1 The collector is in the shape of a roller, the distance between the extrusion tube and the collector is 12 cm to 15 cm, and the collection speed of the roller is 100 rpm to 260 rpm.
[0059] In some embodiments, the external voltage of the electrospinning is 22 kV and the extrusion speed is 2.0 mL·h -1 The collector is in the shape of a roller, the distance between the extrusion tube and the collector is 13 cm, and the collection speed of the roller is 250 rpm.
[0060] In some embodiments, the first blended membrane electrolyte is electrospun on a side of the base membrane close to the positive electrode to a thickness of 0.1 μm to 2 μm, and the second blended membrane electrolyte is electrospun on a side of the base membrane close to the negative electrode to a thickness of 0.2 μm to 0.3 μm.
[0061] In some embodiments, the first blended membrane electrolyte is electrospun to a thickness of 0.1 μm on a side of the base membrane close to the positive electrode, and the second blended membrane electrolyte is electrospun to a thickness of 0.2 μm on a side of the base membrane close to the negative electrode.
[0062] In some embodiments, Figure 2 As shown, a winding needle is used to wind the positive electrode, the negative electrode and the separator provided in the present application into a bare battery cell, and the alignment consistency of the positive and negative electrodes is ensured by correction.
[0063] Embodiment 1: The electrospun nanofibers are dissolved in a polar organic solvent and stirred for 2 hours until the mixture is uniformly mixed to obtain a preliminary electrospinning solution. The mass ratio of the polar organic solvent to the electrospun nanofibers is 10:1, and the polar organic solvent is dimethylformamide.
[0064] A covalent organic framework porous material is added to the prepared electrospinning solution, and the mixture is ultrasonically stirred for 4 hours, and then allowed to stand at room temperature for 6 hours to obtain a first blended membrane electrolyte. A hydrogen bonded organic framework porous material is added to the prepared electrospinning solution, and the mixture is ultrasonically stirred for 4 hours, and then allowed to stand at room temperature for 6 hours to obtain a second blended membrane electrolyte.
[0065] Specifically, in the first blended membrane electrolyte, the mass ratio of the covalent organic framework porous material to the electrospun nanofiber is 1:1; in the second blended membrane electrolyte, the mass ratio of the hydrogen-bonded organic framework porous material to the electrospun nanofiber is 1:1. The covalent organic framework porous material is COF-1; the hydrogen-bonded organic framework porous material is HOF-14. The base membrane is a ceramic base membrane.
[0066] The first blended membrane electrolyte is electrospun on the side of the base membrane close to the positive electrode, and the second blended membrane electrolyte is electrospun on the side of the base membrane close to the negative electrode. Then, a non-polymerizable inorganic gas is used for plasma treatment to obtain a diaphragm. Specifically, the electrospinning process parameters are an external voltage of 10 kV and an extrusion speed of 1 mL·h -1 The collector is in the shape of a roller, the distance between the extrusion tube and the collector is 10 cm, and the collection speed of the roller is 50 rpm. The non-polymerizable inorganic gas is O2, the pressure of the plasma treatment is 80 W, and the treatment time is 40 s. The thickness of the first blended membrane electrolyte electrospun on the side of the base membrane close to the positive electrode is 0.1 μm, and the thickness of the second blended membrane electrolyte electrospun on the side of the base membrane close to the negative electrode is 0.2 μm.
[0067] Finally, the separator, the positive electrode, the negative electrode and the electrolyte are assembled and packaged to obtain the first secondary battery.
[0068] Embodiment 2: The electrospun nanofibers are dissolved in a polar organic solvent and stirred for 4 hours until the mixture is uniformly mixed to obtain a preliminary electrospinning solution. The mass ratio of the polar organic solvent to the electrospun nanofibers is 20:1, and the polar organic solvent is a mixed solvent of dimethylacetamide, dimethyl sulfoxide and cyclopentane.
[0069] A covalent organic framework porous material is added to the prepared electrospinning solution, and the mixture is ultrasonically stirred for 8 hours, and then allowed to stand at room temperature for 8 hours to obtain a first blended membrane electrolyte. A hydrogen bonded organic framework porous material is added to the prepared electrospinning solution, and the mixture is ultrasonically stirred for 8 hours, and then allowed to stand at room temperature for 8 hours to obtain a second blended membrane electrolyte.
[0070] Specifically, in the first blended membrane electrolyte, the mass ratio of the covalent organic framework porous material to the electrospun nanofiber is 40:1; in the second blended membrane electrolyte, the mass ratio of the hydrogen bonded organic framework porous material to the electrospun nanofiber is 40:1. The covalent organic framework porous materials are COF-5, COF-10 and COF-8; the hydrogen bonded organic framework porous materials are HOF-14, HOF-16, ZJU-HOF-1 and ZJU-HOF-10. The base film is a polyethylene PE base film.
[0071] The first blended membrane electrolyte is electrospun on the side of the base membrane close to the positive electrode, and the second blended membrane electrolyte is electrospun on the side of the base membrane close to the negative electrode. Then, a non-polymerizable inorganic gas is used for plasma treatment to obtain a diaphragm. Specifically, the electrospinning process parameters are an external voltage of 25 kV and an extrusion speed of 2.5 mL·h -1 The collector is in the shape of a roller, the distance between the extrusion tube and the collector is 20 cm, and the collection speed of the roller is 300 rpm. The non-polymeric inorganic gas includes N2, CO2 and CO, the pressure of the plasma treatment is 120W, and the treatment time is 120s. The thickness of the first blended membrane electrolyte electrospun on the side of the base membrane close to the positive electrode is 2μm, and the thickness of the second blended membrane electrolyte electrospun on the side of the base membrane close to the negative electrode is 0.3μm.
[0072] Finally, the separator, the positive electrode, the negative electrode and the electrolyte are assembled and packaged to obtain the second secondary battery.
[0073] Embodiment three: The electrospun nanofibers are dissolved in a polar organic solvent and stirred for 3 hours until the mixture is uniformly mixed to obtain a preliminary electrospinning solution. The mass ratio of the polar organic solvent to the electrospun nanofibers is 15:1, and the polar organic solvent is a mixed solvent of ethylene nitrate, diethylformamide and N-methylpyrrolidone.
[0074] A covalent organic framework porous material is added to the preparatory electrospinning solution, ultrasonically stirred for 7 hours, and then allowed to stand at room temperature for 7 hours to obtain a first blended membrane electrolyte; a hydrogen-bonded organic framework porous material is added to the preparatory electrospinning solution, ultrasonically stirred for 6 hours, and then allowed to stand at room temperature for 7 hours to obtain a second blended membrane electrolyte. Specifically, in the first blended membrane electrolyte, the mass ratio of the covalent organic framework porous material to the electrospun nanofiber is 25:1, and in the second blended membrane electrolyte, the mass ratio of the hydrogen-bonded organic framework porous material to the electrospun nanofiber is 30:1. The covalent organic framework porous material is COF-102; the hydrogen-bonded organic framework porous material is HOF-FJU-1. The base film is a polypropylene PP base film.
[0075] The first blended membrane electrolyte is electrospun on the side of the base membrane close to the positive electrode, and the second blended membrane electrolyte is electrospun on the side of the base membrane close to the negative electrode. Then, a non-polymerizable inorganic gas is used for plasma treatment to obtain a diaphragm. Specifically, the electrospinning process parameters are an external voltage of 15 kV and an extrusion speed of 2.0 mL·h -1 The collector is in the shape of a roller, the distance between the extrusion tube and the collector is 15 cm, and the collection speed of the roller is 250 rpm. The non-polymerizable inorganic gas includes CO and H2O, the pressure of the plasma treatment is 100 W, and the treatment time is 70 s. The thickness of the first blended membrane electrolyte electrospun on the side of the base membrane close to the positive electrode is 1 μm, and the thickness of the second blended membrane electrolyte electrospun on the side of the base membrane close to the negative electrode is 0.25 μm.
[0076] Finally, the separator, the positive electrode, the negative electrode and the electrolyte are assembled and packaged to obtain the third secondary battery.
[0077] Embodiment 4: The electrospun nanofibers are dissolved in a polar organic solvent and stirred for 2 hours until the mixture is uniformly mixed to obtain a preliminary electrospinning solution. The mass ratio of the polar organic solvent to the electrospun nanofibers is 12:1, and the polar organic solvent is a mixed solvent of dimethylformamide, dimethylacetamide, dimethyl sulfoxide and sulfolane.
[0078] A covalent organic framework porous material is added to the preparatory electrospinning solution, ultrasonically stirred for 8 hours, and then allowed to stand at room temperature for 7 hours to obtain a first blended membrane electrolyte; a hydrogen-bonded organic framework porous material is added to the preparatory electrospinning solution, ultrasonically stirred for 4 hours, and then allowed to stand at room temperature for 6 hours to obtain a second blended membrane electrolyte. Specifically, in the first blended membrane electrolyte, the mass ratio of the covalent organic framework porous material to the electrospun nanofiber is 26:1, and in the second blended membrane electrolyte, the mass ratio of the hydrogen-bonded organic framework porous material to the electrospun nanofiber is 31:1. The covalent organic framework porous material is COF-8; the hydrogen-bonded organic framework porous materials are HOF-14, HOF-16 and ZJU-HOF-1. The base film is a polypropylene / polyethylene / polypropylene multilayer base film.
[0079] The first blended membrane electrolyte is electrospun on the side of the base membrane close to the positive electrode, and the second blended membrane electrolyte is electrospun on the side of the base membrane close to the negative electrode. Then, a non-polymerizable inorganic gas is used for plasma treatment to obtain a diaphragm. Specifically, the electrospinning process parameters are an external voltage of 22 kV and an extrusion speed of 2.3 mL·h -1The collector is in the shape of a roller, the distance between the extrusion tube and the collector is 13 cm, and the collection speed of the roller is 260 rpm. The non-polymerizable inorganic gas is CO2, CO and H2O, the pressure of the plasma treatment is 110W, and the treatment time is 70s. The thickness of the first blended membrane electrolyte electrospun on the side of the base membrane close to the positive electrode is 1.5μm, and the thickness of the second blended membrane electrolyte electrospun on the side of the base membrane close to the negative electrode is 0.3μm.
[0080] Finally, the separator, the positive electrode, the negative electrode and the electrolyte are assembled and packaged to obtain the fourth secondary battery.
[0081] Embodiment five: The electrospun nanofibers are dissolved in a polar organic solvent and stirred for 2 hours until the mixture is uniformly mixed to obtain a preliminary electrospinning solution. The mass ratio of the polar organic solvent to the electrospun nanofibers is 13:1, and the polar organic solvent is a mixed solvent of dimethylformamide, dimethylacetamide dimethyl sulfoxide, cyclopentane, ethyl nitrate, diethylformamide and N-methylpyrrolidone.
[0082] A covalent organic framework porous material is added to the preparatory electrospinning solution, ultrasonically stirred for 4 hours, and then allowed to stand at room temperature for 8 hours to obtain a first blended membrane electrolyte; a hydrogen bonded organic framework porous material is added to the preparatory electrospinning solution, ultrasonically stirred for 6 hours, and then allowed to stand at room temperature for 8 hours to obtain a second blended membrane electrolyte. Specifically, in the first blended membrane electrolyte, the mass ratio of the covalent organic framework porous material to the electrospun nanofiber is 25:1, and in the second blended membrane electrolyte, the mass ratio of the hydrogen bonded organic framework porous material to the electrospun nanofiber is 40:1. The covalent organic framework porous materials are COF-1, COF-5, COF-10, COF-8 and COF-102; the hydrogen bonded organic framework porous materials are HOF-14, HOF-16, ZJU-HOF-1, ZJU-HOF-10 and HOF-FJU-1. The base film is a PET base film.
[0083] The first blended membrane electrolyte is electrospun on the side of the base membrane close to the positive electrode, and the second blended membrane electrolyte is electrospun on the side of the base membrane close to the negative electrode. Then, a non-polymerizable inorganic gas is used for plasma treatment to obtain a diaphragm. Specifically, the electrospinning process parameters are an external voltage of 25 kV and an extrusion speed of 2.5 mL·h -1, the collector is in the shape of a roller, the distance between the extrusion tube and the collector is 10 cm, and the collection speed of the roller is 300 rpm. The non-polymeric inorganic gas includes O2, N2, CO2, CO and H2O, the pressure of the plasma treatment is 120W, and the treatment time is 120s. The thickness of the first blended membrane electrolyte electrospun on the side of the base membrane close to the positive electrode is 0.1μm, and the thickness of the second blended membrane electrolyte electrospun on the side of the base membrane close to the negative electrode is 0.3μm.
[0084] Finally, the separator, the positive electrode, the negative electrode and the electrolyte are assembled and packaged to obtain the fifth secondary battery.
[0085] Comparative Example 1: The electrospun nanofibers are dissolved in a polar organic solvent and stirred for 4 hours until the mixture is uniformly mixed to obtain a preliminary electrospinning solution. The mass ratio of the polar organic solvent to the electrospun nanofibers is 30:1, and the polar organic solvent is ethylene nitrate.
[0086] A covalent organic framework porous material is added to the prepared electrospinning solution, and the mixture is ultrasonically stirred for 3 hours, and then allowed to stand at room temperature for 5 hours to obtain a first blended membrane electrolyte. A hydrogen bonded organic framework porous material is added to the prepared electrospinning solution, and the mixture is ultrasonically stirred for 3 hours, and then allowed to stand at room temperature for 5 hours to obtain a second blended membrane electrolyte.
[0087] Specifically, in the first blended membrane electrolyte, the mass ratio of the covalent organic framework porous material to the electrospun nanofiber is 50:1, and in the second blended membrane electrolyte, the mass ratio of the hydrogen-bonded organic framework porous material to the electrospun nanofiber is 20:1. The covalent organic framework porous material is COF-1; the hydrogen-bonded organic framework porous material is HOF-14. The base membrane is a polyacrylonitrile PAN base membrane.
[0088] The first blended membrane electrolyte is electrospun on the side of the base membrane close to the positive electrode, and the second blended membrane electrolyte is electrospun on the side of the base membrane close to the negative electrode. Then, a non-polymerizable inorganic gas is used for plasma treatment to obtain a diaphragm. Specifically, the electrospinning process parameters are an external voltage of 25 kV and an extrusion speed of 2.5 mL·h -1 The collector is a roller, the distance between the extrusion tube and the collector is 10 cm, and the collection speed of the roller is 50 rpm. The non-polymerizable inorganic gas is O2, the pressure of the plasma treatment is 80 W, and the treatment time is 40 s.
[0089] The first blended membrane electrolyte is electrospun on the side of the base membrane close to the positive electrode to a thickness of 0.1 μm, and the second blended membrane electrolyte is electrospun on the side of the base membrane close to the negative electrode to a thickness of 0.1 μm.
[0090] Finally, the separator, the positive electrode, the negative electrode and the electrolyte are assembled and packaged to obtain the first comparative secondary battery.
[0091] Comparative Example 2: The electrospinning nanofibers are dissolved in a polar organic solvent and stirred until uniformly mixed to obtain a preliminary electrospinning solution. The mass ratio of the polar organic solvent to the electrospinning nanofibers is 5:1, and the polar organic solvent is a mixed solvent of ethylene nitrate and N-methylpyrrolidone.
[0092] A covalent organic framework porous material is added to the prepared electrospinning solution, and after ultrasonic stirring for 2 hours, the solution is allowed to stand at room temperature for 10 hours to obtain a first blended membrane electrolyte. Specifically, in the first blended membrane electrolyte, the mass ratio of the covalent organic framework porous material to the electrospun nanofiber is 10:1. The covalent organic framework porous material is COF-5; and the base membrane is a glass fiber base membrane.
[0093] The first blended membrane electrolyte is electrospun on the side of the base membrane close to the positive electrode, and then plasma treated with a non-polymerizable inorganic gas to obtain a diaphragm. Specifically, the electrospinning process parameters are an external voltage of 10 kV and an extrusion speed of 2.5 mL·h -1 The collector is in the shape of a roller, the distance between the extrusion tube and the collector is 10 cm, and the collection speed of the roller is 300 rpm.
[0094] The non-polymerizable inorganic gas is O2, the pressure of the plasma treatment is 80W, and the treatment time is 120s. The first blended membrane electrolyte is electrospun to a thickness of 0.1 μm on the side of the base membrane close to the positive electrode, and the second blended membrane electrolyte is electrospun to a thickness of 0.1 μm on the side of the base membrane close to the negative electrode.
[0095] Finally, the separator, the positive electrode, the negative electrode and the electrolyte are assembled and packaged to obtain the second comparative secondary battery.
[0096] The properties of the diaphragms prepared in Example 1, Example 2, Example 3, Example 4, Example 5, Comparative Example 1 and Comparative Example 2 are shown in Table 3.
[0097] Among them, the air permeability refers to the time required for 100mL of air to pass through a 6.45cm² diaphragm under a pressure of 1.21kPa; the porosity refers to the volume percentage of pores in the diaphragm; the liquid absorption rate refers to taking a diaphragm with a mass of m0, soaking it in a typical electrolyte for a certain period of time, and then naturally drying it to weigh a mass of m1, and the liquid absorption rate = (m1-m0) / m0; the shrinkage rate refers to the rate of change of the size of the diaphragm after heating, which is divided into longitudinal (MD) shrinkage rate and transverse (TD) shrinkage rate. Table 3 shows the results of heating at 150℃ for 1 hour and measuring the size change of the diaphragm before and after heating.
[0098] In order to measure the volume change of the secondary battery caused by swelling due to internal gas production, the 2.2Ah soft-pack batteries prepared in the above embodiments and comparative examples were fully charged and stored at 85°C for 8 weeks. The volume expansion of the soft pack was monitored regularly, and the volume change of the soft pack was tested by the water displacement method. The results are shown in Table 4.
[0099] Table 3 Diaphragm performance
[0100] Table 4 Battery volume change experimental results
[0101] According to the experimental results, coating hydrogen-bonded organic framework porous materials and covalent organic framework porous materials on both sides of the base film can effectively reduce the volume change of the battery due to internal gas production by adsorbing gas. And compared with coating organic framework porous materials on both sides of the base film for gas adsorption, coating only on one side significantly increases the volume change of the battery. Therefore, the secondary battery provided by the present application has a gas absorption effect and reduces the volume change of the battery. Solve the problem of battery performance deterioration caused by internal gas production in the battery and affecting the safe use of the battery.
[0102] The present application provides a secondary battery and a method for preparing the same. The secondary battery includes a positive electrode, a negative electrode, an electrolyte and a diaphragm, wherein the diaphragm is arranged between the positive electrode and the negative electrode, and the diaphragm includes a base membrane, a first porous coating is arranged on the side of the base membrane close to the positive electrode, and the first porous coating includes a covalent organic framework porous material, and a second porous coating is arranged on the side of the base membrane close to the negative electrode, and the second porous coating includes a hydrogen bond organic framework porous material. Organic porous framework materials with different gas adsorption properties are coated on both sides of the base membrane, and these porous materials have certain specificity and high efficiency for gas adsorption. For example, the porous material coated on the base membrane close to the positive electrode side has a strong adsorption effect on gases such as CO2, CO, and O2, and the porous material coated on the base membrane close to the negative electrode side has a good adsorption effect on the above-mentioned alkane and olefin gases. The above materials can effectively adsorb gases and solve the problem of battery performance deterioration caused by gas production inside the battery and affecting the safe use of the battery.
[0103] Similar parts between the embodiments provided in this application can be referenced to each other. The specific implementation methods provided above are only a few examples under the general concept of this application and do not constitute a limitation on the protection scope of this application. For those skilled in the art, any other implementation methods expanded based on the scheme of this application without creative work belong to the protection scope of this application.
Claims
1. A secondary battery, characterized in that: The secondary battery comprises: A positive electrode, a negative electrode, an electrolyte and a diaphragm, wherein the diaphragm is arranged between the positive electrode and the negative electrode, the diaphragm comprises a base membrane, a first porous coating is arranged on a side of the base membrane close to the positive electrode, the first porous coating comprises a covalent organic framework porous material, and a second porous coating is arranged on a side of the base membrane close to the negative electrode, the second porous coating comprises a hydrogen bond organic framework porous material.
2. The secondary battery according to claim 1, characterized in that: The thickness of the first porous coating layer is 0.1 μm to 2 μm, the thickness of the second porous coating layer is 0.2 μm to 0.3 μm, and the thickness of the base film is 4 μm to 30 μm.
3. The secondary battery according to claim 1, characterized in that: The covalent organic framework porous material is one or more of COF-1, COF-5, COF-10, COF-8 or COF-102.
4. The secondary battery according to claim 1, characterized in that: The hydrogen-bonded organic framework porous material is one or more of HOF-14, HOF-16, ZJU-HOF-1, ZJU-HOF-10 or HOF-FJU-1.
5. The secondary battery according to claim 1, characterized in that: The base film is a ceramic base film, a polyethylene base film, a polypropylene base film, a polypropylene / polyethylene / polypropylene multilayer base film, a polyethylene terephthalate base film, a polyacrylonitrile base film, a glass fiber base film, a cellulose base film, a polyvinylidene fluoride based film, a polyolefin film or a non-woven fabric diaphragm.
6. A method for preparing a secondary battery, for preparing the secondary battery according to any one of claims 1 to 5, characterized in that: include: The electrospinning nanofibers are dissolved in a polar organic solvent and stirred to obtain a preparatory electrospinning solution; Adding a covalent organic framework porous material to part of the prepared electrospinning solution, stirring, and obtaining a first blended membrane electrolyte; Adding the hydrogen-bonded organic framework porous material to the remaining prepared electrospinning solution and stirring to obtain a second blended membrane electrolyte; Electrospinning the first blended membrane electrolyte on the side of the base membrane close to the positive electrode, and electrospinning the second blended membrane electrolyte on the side of the base membrane close to the negative electrode, and performing plasma treatment to obtain a separator; The separator, the positive electrode, the negative electrode and the electrolyte are assembled and packaged to obtain a secondary battery.
7. The method according to claim 6, characterized in that Also includes: The electrospun nanofibers are dissolved in a polar organic solvent, and stirred for 2 to 4 hours until the mixture is uniformly mixed to obtain a preliminary electrospinning solution, wherein the mass ratio of the polar organic solvent to the electrospun nanofibers is 10:1 to 20:1, and the polar organic solvent is one or more of dimethylformamide, dimethylacetamide dimethyl sulfoxide, cyclopentane, ethyl nitrate, diethylformamide, and N-methylpyrrolidone; Adding the covalent organic framework porous material to part of the prepared electrospinning solution, stirring for 4 hours to 8 hours with ultrasonic stirring, and then standing at room temperature for 6 hours to 8 hours to obtain a first blended membrane electrolyte; Adding the hydrogen-bonded organic framework porous material to the remaining prepared electrospinning solution, stirring ultrasonically for 4 hours to 8 hours, and then standing at room temperature for 6 hours to 8 hours to obtain a second blended membrane electrolyte; The first blended membrane electrolyte is electrospun on the side of the base membrane close to the positive electrode, and the second blended membrane electrolyte is electrospun on the side of the base membrane close to the negative electrode, and a diaphragm is obtained after plasma treatment with a non-polymerizable inorganic gas, wherein the non-polymerizable inorganic gas includes one or more of O2, N2, CO2, CO, and H2O, and the pressure of the plasma treatment is 80W to 120W, and the treatment time is 40s to 120s; The separator, the positive electrode, the negative electrode and the electrolyte are assembled and packaged to obtain the secondary battery.
8. The method according to claim 6, characterized in that In the first blended membrane electrolyte, the mass ratio of the covalent organic framework porous material to the electrospun nanofibers is 1:1 to 40:1, and in the second blended membrane electrolyte, the mass ratio of the hydrogen bonded organic framework porous material to the electrospun nanofibers is 1:1 to 40:
1.
9. The method according to claim 6, characterized in that The external voltage of the electrospinning was 10 kV~25 kV, and the extrusion speed was 1 mL·h -1 ~2.5 mL·h -1 The collector is in the shape of a roller, the distance between the extrusion tube and the collector is 10 cm to 20 cm, and the collection speed of the roller is 50 rpm to 300 rpm.
10. The method according to claim 6, characterized in that The first blended membrane electrolyte is electrospun on the side of the base membrane close to the positive electrode to a thickness of 0.1 μm to 2 μm, and the second blended membrane electrolyte is electrospun on the side of the base membrane close to the negative electrode to a thickness of 0.2 μm to 0.3 μm.
Citation Information
Patent Citations
Carbazolyl hydrogen-bond organic frame material as well as preparation method and application thereof
CN109134882A
Preparation method and application of hydrogen bond self-assembled microporous organic framework
CN117209789A
Multilayer polymeric membrane and process
US20180065105A1
Functional coating material for lithium ion battery separator and preparation method therefor
WO2021089016A1
Separator, secondary battery, and electric device
WO2024174068A1
Cited By
Asymmetric coating diaphragm based on compounding of porous material and ceramic material
CN119447707A
Preparation method of diaphragm of secondary battery and secondary battery
CN119824609A
